Pemenuhan Hak Pendidikan Anak Menurut UU No. 35 Tahun 2014 Tentang Perlindungan Anak - Uyun Ayunda, Amalia; Yustitianingtyas, Levina (DOKTRINA: JOURNAL OF LAW, 2025)
The issue of unequal education rights for children is often a crucial problem. Because education is considered as a guide to change, both in terms of individuals and countries. This is the responsibility of the government in realizing equal distribution of the right to education in sync with the enactment of these regulations. Therefore, the formulation of the problem in this study is how the role and efforts of the government in fulfilling the right to education. So that the purpose of this study, to understand the role and efforts made by the government in overcoming the problems of the right to education caused by obstacles, and have an impact on the non-fulfillment of the right to education. This research is a normative juridical research that uses a statutory approach. Based on the results of this research, the government issued educational programs and made changes to aspects of education that became obstacles.